Radioelement Distribution in River, Beach, and Offshore Areas and Their Significance to Chavara Placer Deposit, Southern Kerala Coast of India - T. N. Prakash, G. K. Raju, and M. Prithviraj (Geo-Marine Letters ( 1991 ) 11:32-38, 1991)
The radioelement and heavy mineral distribution in river, beach and innershelf areas of the southern Kerala coast is related to placer mineral concentration on the beaches at Chavara. Southern Kerala rivers--Neyyar, Karamana and Vamanapuram-- transport higher amounts of radioactive elements than the larger Kallada River due to higher radioactive minerals in the hinterland rocks. Coastal configurations and the seasonal longshore current pattern seems to control along-shore distribution of minerals. The proposed model for placer concentration suggests that the energy difference and seasonal current direction along this coast is important.